Розробка та аналіз параметрів фільтрувальних ланцюгів для обробки сигналів у цифрових системах - Бібік, С. М. (ХНУРЕ, 2025)
In modern digital systems, signal processing plays a key role in ensuring the accuracy and efficiency of technologies. One of the main tasks is noise filtering, which enhances signal quality and extracts useful information. This paper examines spectral subtraction as a noise reduction method, particularly its application to audio signals. The use of Fourier Transform (FFT/STFT), adaptive and bandpass filters, as well as the Wiener filter, is described. The advantages of spectral subtraction, especially its effectiveness for stationary noise, are highlighted, along with its limitations related to artifacts and non-stationary noise.
Keywords: фільтрувальний ланцюг; обробка сигналів